Scripting cultures : architectural design and programming - Burry, Mark; Ohio Library and Information Network (Chichester, UK : Wiley, 2011)
With scripting, computer programming becomes integral to the digital design process. It provides unique opportunities for innovation, enabling the designer to customise the software around their own predilections and modes of working. It liberates the designer by automating many routine aspects and repetitive activities of the design process, freeing-up the designer to spend more time on design thinking. Software that is modified through scripting offers a range of speculations that are not possible using the software only as the manufacturers intended it to be used
Machine generated contents note: ch. 1 Scripting cultures -- ch. 2 Contextual summary of computing, scripting and speculative design -- ch. 3 Cultural defence -- ch. 4 Resources -- ch. 5 Dimensions -- ch. 6 Scripted productivity: Gaudi's rose windows -- ch. 7 Composition and form -- ch. 8 Simplifying complexity for fabrication -- ch. 9 Scripting narrative space: Our World and The Third Policeman -- ch. 10 Performative scripting -- ch. 11 Cultural account: scripting and shifts in authorship
Includes bibliographical references and index
Keywords: Architectural design; Computer-aided design; Architectural models; Architecture, Modern -- 21st century; Electronic books